2020
DOI: 10.1016/j.aquatox.2020.105607
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to environmentally relevant lead levels induces oxidative stress and neurobehavioral alterations in larval zebrafish (Danio rerio)

Abstract: The ubiquitous contamination of environmental lead (Pb) remains a worldwide threat.Improper Pb mine waste disposal from an abandoned lead-zinc mine has recently unearthed a widespread Pb poisoning in children in Kabwe Zambia. Although the adverse effects of Pb on human health have begun to receive attention, the ecotoxicological effects on aquatic vertebrates still need further investigation. In addition, there is paucity in the knowledge on the behavioural and molecular subcellular responses in larval zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
2
15
2
Order By: Relevance
“…In zebrafish embryos, it has been previously reported that short-term exposure to high Pb concentrations induces increased ROS production and upregulation of the antioxidant enzymes [51]. We showed that two environmentally relevant concentrations of Pb induce a significant and time-dependent upregulation of sod1, a key antioxidant enzyme implicated in the first-line defense against oxidative stress [35,47,51,53,69,70]. Since Pb concentrations tested here are very low, our results reinforce the role of sod as sensitive and valuable biomarkers of lead-induced oxidative stress with important consequences thereof for the protection of aquatic life and human health.…”
Section: Gene-expressionmentioning
confidence: 57%
See 2 more Smart Citations
“…In zebrafish embryos, it has been previously reported that short-term exposure to high Pb concentrations induces increased ROS production and upregulation of the antioxidant enzymes [51]. We showed that two environmentally relevant concentrations of Pb induce a significant and time-dependent upregulation of sod1, a key antioxidant enzyme implicated in the first-line defense against oxidative stress [35,47,51,53,69,70]. Since Pb concentrations tested here are very low, our results reinforce the role of sod as sensitive and valuable biomarkers of lead-induced oxidative stress with important consequences thereof for the protection of aquatic life and human health.…”
Section: Gene-expressionmentioning
confidence: 57%
“…Several endpoints have been evaluated to disclose signals of lead toxicity in fish sentinel species, including zebrafish. Neurotoxicity, oxidative stress induction, and hematological alterations are the mainly reported outcomes of lead exposure in both adults and embryos [8,[22][23][24]29,30,34,[44][45][46][47]. However, all these literature data relate to high lead concentrations, thus leaving a gap of knowledge regarding the adverse effects of lead at environmentally relevant concentrations [9,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent testing at six Washington DC public schools in 2008 showed that 2–41% of sampled tap water has a Pb contamination problem, with the highest lead detected at 1987 μg L −1 , significantly higher than the EPA-recommended maximum level of 20 μg L −1 for schools [ 13 ]. As it is described in literature, in addition to its major neurotoxicity [ 14 , 15 , 16 , 17 , 18 , 19 ] the exposure to Pb has been linked to oxidative stress [ 20 ], cardiovascular toxicity [ 21 ], as well as gut microbiota dysbiosis and hepatic metabolic disorder [ 12 ] in zebrafish. Among the Pb-induced zebrafish neurobehavioral changes identified to date, learning and memory deficits, a decrease in the exploratory activities, altered social and aggressive behavior, color preference or responses to mechanosensory and visual stimuli are included [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DM concentration in water samples ranged from ng L −1 to μg L −1 . Previous studies have reported that DM exposure could induce zebrafish developmental delay and malformation [ 38 , 39 , 40 ], apoptosis [ 38 , 40 ], cardiovascular toxicity [ 38 ], gonadotoxicity [ 41 ] as well as changes in neurochemical, behavioral and cognitive endpoints [ 20 , 38 , 39 , 42 , 43 , 44 ]. Hyperactivity and swimming towards the surfaces were observed in adult zebrafish after DM (>0.1 μg L −1 ) exposure [ 39 , 45 ].…”
Section: Introductionmentioning
confidence: 99%